2016
DOI: 10.1259/dmfr.20150391
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography (CT) in the selection of treatment for root-filled maxillary molars with apical periodontitis

Abstract: The endodontists in this study exhibited a low degree of agreement when choosing a treatment for root-filled maxillary molars with apical periodontitis. A CT examination of the investigated teeth did not result in a significantly higher degree of agreement, and CT frequently contributed to a shift in the selected therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
2
0
2
Order By: Relevance
“…This led experts in four out of five cases to decide for a treatment to eradicate the OIF, mainly through a surgical approach. This is in agreement with previous studies in endodontics and orthodontics showing that CBCT could lead to a more invasive treatment ( 17 - 20 ). The only case for which experts recommended therapeutic abstention was Case 3: incomplete endodontic treatment without apical periodontitis.…”
Section: Discussionsupporting
confidence: 93%
“…This led experts in four out of five cases to decide for a treatment to eradicate the OIF, mainly through a surgical approach. This is in agreement with previous studies in endodontics and orthodontics showing that CBCT could lead to a more invasive treatment ( 17 - 20 ). The only case for which experts recommended therapeutic abstention was Case 3: incomplete endodontic treatment without apical periodontitis.…”
Section: Discussionsupporting
confidence: 93%
“…It was found that 33 (40%) of the root filled teeth with signs of post-treatment disease at first examination had been retreated or extracted, while the remaining 49 teeth had received no radiographically detectable treatment. Similar observations continue to be published and the overall conclusion is that there is no consensus about how to deal with post-treatment disease (Çiçek et al, 2016;Kirkevang et al, 2014;Mota de Almeida et al, 2016;Taha et al, 2019).…”
Section: How Decisions About Post-treatment Disease Are Madementioning
confidence: 77%
“…Since several studies have demonstrated large inter‐ and intraindividual variation in interpretation of the periapical area in radiographs (Petersson et al, 2012) it has been hypothesized that variation in retreatment decisions might be regarded as a function of diagnostic variation. However, neither studies among general practitioners (Reit & Gröndahl, 1987) nor specialists (Mota de Almeida et al, 2016) have given support to this idea.…”
Section: How Decisions About Post‐treatment Disease Are Madementioning
confidence: 99%
“…Imagens tomográficas têm qualidade superior quando comparadas às radiografias periapicais e panorâmicas na detecção de lesões periapicais [5,6,20]. Para alguns autores, a TCFC gera aumento da exposição de radiação quando comparada aos exames radiográficos, além de ser mais dispendiosa, devendo ser evitada ou usada, quando possível, de forma pontual [16,17,20], entretanto a dose de radiação gerada pela tomografia com campo de visão pequeno é próxima à dose de radiação de uma radiografia panorâmica. De acordo com a alta prevalência de canais MV2 não tratados e a variabilidade anatômica dos primeiros molares superiores, a TCFC poderia ser sugerida como padrão ouro para o diagnóstico [19,20].…”
Section: Discussionunclassified